2021
DOI: 10.1186/s40538-021-00211-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous immunoassay strategy for enhancing detection sensitivity of banned dye rhodamine B in fraudulent food

Abstract: Background The high quality of antibody (Ab) is critical for an immunoassay; usually, an Ab with low affinity is often regarded as a “bad” one in the immunoassay development. How to use a “bad” Ab to develop a highly sensitive immunoassay is still a huge challenge. Methods In this study, a heterologous immunoassay strategy was designed to enhance the sensitivity for the detection of banned dye, rhodamine B (RB), in fraudulent food. The RB Ab could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…3) confirmed that antibodies from the antiserum to Amp-pPh-TG were more sensitive to penicillin antibiotics than polyclonal antibodies from the antiserum to Amp-rhLF. In line with observations by Wang et al [21], we found additionally that better immunoanalytical parameters were ensured by heterologous immunogen and conjugated antigen constructs, which differed in the structure of the hapten used for their synthesis. In the case of the antiserum to Amp-pPh-TG, the effect was observed both when the haptenprotein linker differed between the constructs and when the linker was the same, but the constructs included Amp or Amox.…”
Section: Immunogenic Aminopenicillin Conjugates and Generation Of Pol...supporting
confidence: 91%
“…3) confirmed that antibodies from the antiserum to Amp-pPh-TG were more sensitive to penicillin antibiotics than polyclonal antibodies from the antiserum to Amp-rhLF. In line with observations by Wang et al [21], we found additionally that better immunoanalytical parameters were ensured by heterologous immunogen and conjugated antigen constructs, which differed in the structure of the hapten used for their synthesis. In the case of the antiserum to Amp-pPh-TG, the effect was observed both when the haptenprotein linker differed between the constructs and when the linker was the same, but the constructs included Amp or Amox.…”
Section: Immunogenic Aminopenicillin Conjugates and Generation Of Pol...supporting
confidence: 91%
“…Since the heterologous coating antigens frequently cause a minor decrease in antibody recognition when compared to the homogeneous coating antigen, analytes can be competed with the heterogeneous coating antigen at lower concentrations and achieve better sensitivity. 30 Similarly, in this study, the inhibition ratios of the antisera to 6-BA was improved by the use of heterologous coating antigens. The highest inhibition ratio of 90% for 6-BA was obtained from hapten 1-BSA when hapten 1-BSA was paired with hapten 2-OVA, which was utilized as the coating antigen (Table S1).…”
Section: Characterization Of the Anti-6-ba Polyclonal Serummentioning
confidence: 63%
“…In addition, it is generally understood that heterologous coating antigens typically lead to enhanced sensitivity and lower immunoreagent dilution in icELISA. Since the heterologous coating antigens frequently cause a minor decrease in antibody recognition when compared to the homogeneous coating antigen, analytes can be competed with the heterogeneous coating antigen at lower concentrations and achieve better sensitivity . Similarly, in this study, the inhibition ratios of the antisera to 6-BA was improved by the use of heterologous coating antigens.…”
Section: Results and Discussionmentioning
confidence: 82%
“…However, a thorough safety evaluation has provided sufficient evidence to suggest that Rh B contamination irritates the skin, eyes, and respiratory tract and even causes carcinogenic and teratogenic effects on public health. [11][12][13] To achieve highly sensitive detection of Rh B, various methods have been proposed, such as surface-enhanced Raman scattering (SERS), 14,15 electrochemical detection, 16 enzyme-linked immunosorbent assay (ELISA), 17 and high-performance liquid chromatography (HPLC). 18 Optical evanescent-wave (EW) sensors have attracted considerable attention owing to their features including immunity to electromagnetic interference, electrical insulation, high corrosion resistance, and low attenuation over a long distance.…”
Section: Introductionmentioning
confidence: 99%